Invisible voices: experiences and perceptions of mothers and grandmothers caring for newborns with neonatal abstinence syndrome. Issue 1 (19th February 2023) - Lao, Amberly; Li, Tessa; Battaglia, Sarah; Berry, Jessica; Artigas, Valarie; Cong, Xiaomei
Abstract: Objective: This study was designed to give mothers with opioid use disorder (OUD) and their families a "voice" in sharing their experiences surrounding the relationship with health care staff in the care of their newborn with neonatal abstinence syndrome (NAS) and aimed to identify their perceptions of the care received during their newborn's hospitalization. Methods: A cross-sectional study was administered through Qualtrics online survey software. The survey questions with quantitative and qualitative components were developed and validated by the researchers to explore perceptions and experiences regarding the care the mother and the infant received, and their feelings about whether they were adequately educated and prepared to care for themselves and infant with NAS. A convenience sampling method was used to recruit mothers (18 years old and above) who gave birth to infants with NAS as well as their family members from the Department of Behavioral and Community Health in the Northeastern United States. Descriptive analysis methods were used to describe the quantitative survey data and thematic content analysis approach was used to explore the qualitative narrative data. Results: Twenty mothers were eligible for the study and a total of 10 mothers and 3 grandmothers participated in the final study. Primary outcomes for quantitative results from mothers were frustration based on how they were treated, the belief that the newborn required the neonatal intensive care unit, and the conclusion that they were treated inferiorly compared with mothers without OUD. Four major themes identified by the mothers were: judgment by the health care providers, trying to be a good mother, education needs of mothers to receive more information about NAS, and not understood by the health care providers and the need for training specified to caring for OUD during pregnancy and NAS. Results of the grandmothers' study demonstrated a deficiency in personal knowledge about caring for an infant with NAS, and a belief that the mother was treated poorly due to her history. Conclusions: Women with OUD are blamed and stigmatized for their decisions and experience a lack of knowledge in caring for their infants. While further research is warranted in exploring these topics, the disparities between this population and health care providers may increase health risks for both the mother and newborn.